Stefan Zweig entre a literatura e o cinema: representações do exílio - Oliveira, Isabela Almeida de (2017)
Few people know who Stefan Zweig was and how important he is to world literature. Author of several literary, autobiographical, biographical and novelistic works, the Austrian Jewish writer came definitively to Brazil in 1941 with his wife, Lotte, looking for exile, because at that moment Austria and the other countries of Europe were under Hitler's totalitarian power. This dissertation aims to understand a little about the life and work of Stefan Zweig, especially during his trajectory of exile and his last days of life in Brazil, which ended with the tragedy of the suicide of Zweig and Lotte, In Petropolis, Rio de Janeiro, a few days after the Carnival of 1942. For a better understanding of the trajectory of this writer, a brief historical analysis was made of anti-Semitism in Europe and Brazil, especially during the period in which Zweig exiled himself in this country and in some European cities. The text also brings to the reader the different images that were constructed on the person of Zweig in the biography Death in the Paradise, written by Alberto Dines, in 1981, and in the perspective of the cinematographic adaptation, in the film Lost Zweig, produced by the Brazilian film director Sylvio Back, launched in the year 2003. This research is developing in a parallel with brief analyzes on the themes biography, autobiography, adaptation, exile and anti-Semitism, which are the central ideas discussed throughout the text, keeping Stefan Zweig as object of study. Several works that deal with the themes already mentioned have been read, such as “Is it a man?”, By Primo Levi, “Antisemitism in the Vargas Era”, by Maria Luiza Tucci Carneiro, “Brazil, a country of the future” by Stefan Zweig, “A theory of adaptation”, by Linda Hutcheon, among others. Various works and documentaries were studied. Besides that, a field survey was also carried out on a visit to the Memorial of Jewish Immigration, inaugurated in 2016 in São Paulo, which provided a great knowledge about the history of Jewish immigration in Brazil and contributed essentially for the development and conclusion of this work.